2016
DOI: 10.1002/casp.2291
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Identity and the Expression of Depression: A Social Identity Perspective

Abstract: The present research interrogates the greater tendency for Chinese people to somaticize depression relative to Westerners. Drawing from a social identity perspective, three studies were conducted examining the role that cultural norms play in symptom expression. In an initial study, we confirmed greater somatization, minimization of distress and suppression of emotional expression among Chinese participants compared with Australians (Study 1). Asian normative expectations of collectivism moderated these effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 58 publications
(73 reference statements)
4
47
1
1
Order By: Relevance
“…At face value, there seems to be a high variability in effect sizes between individual studies (as the present meta‐analysis shall confirm). Even though correlations between social identity and depression appear to be negative in some large studies (e.g., Sani et al., ), a few studies found non‐significant correlations or even positive correlations between social identity and depression (e.g., Ai, Nicdao, Appel, & Lee, ; Chang, Jetten, Cruwys, & Haslam, ). To describe the magnitude of this heterogeneity, and to seek to explain it, is a prime goal for a meta‐analysis that integrates these findings.…”
Section: Empirical Evidence and The Need For A Meta‐analysismentioning
confidence: 99%
“…At face value, there seems to be a high variability in effect sizes between individual studies (as the present meta‐analysis shall confirm). Even though correlations between social identity and depression appear to be negative in some large studies (e.g., Sani et al., ), a few studies found non‐significant correlations or even positive correlations between social identity and depression (e.g., Ai, Nicdao, Appel, & Lee, ; Chang, Jetten, Cruwys, & Haslam, ). To describe the magnitude of this heterogeneity, and to seek to explain it, is a prime goal for a meta‐analysis that integrates these findings.…”
Section: Empirical Evidence and The Need For A Meta‐analysismentioning
confidence: 99%
“…While some studies have found that depressive symptoms vary across regions based on a series of different factors (e.g., Botha, Shamblaw, & Dozois, 2017;Steptoe, Tsuda, Tanaka, & Wardle, 2007), elevated expressions of depressive symptoms among international students may be determined by the level of internalized cultural identity they carry from their home cultures (Chang, Jetten, Cruwys, & Haslam, 2017). Steptoe et al (2007) compared depressive symptoms in college students across 23 different countries and found a pattern of higher depressive symptoms in non-Western countries, with especially elevated rates in individuals from Pacific Asian societies.…”
Section: Introductionmentioning
confidence: 99%
“…For the Malay group, lower levels of compartmentalization (i.e., less incongruity and categorization of positive and negative information) were associated with depression. These findings support recent conceptual frameworks (Hwang, Myers, Abe‐Kim, & Ting, ; Jobson, ; Wong, Tran, Kim, Van Horn Kerne, & Calfa, ) and empirical findings (Chang et al ., ) that indicate that cultural norms, beliefs, and expectations shape psychological disorders. Specifically in this instance, if the autobiographical life story is compartmentalized in a manner which is contrary to the cultural norm, it may play a role in shaping depression.…”
Section: Discussionmentioning
confidence: 99%